Effectiveness Comparisons of Drug Therapy on Chronic Subdural Hematoma Recurrence: A Bayesian Network Meta-Analysis and Systematic Review - Yu, Wanli; Chen, Weifu; Jiang, Yongxiang; Ma, Mincai; Zhang, Wei; Zhang, Xiaolin; Cheng, Yuan (Frontiers in Pharmacology, 2022)
Objectives: We aim to compare the effectiveness of different drug treatments in improving the recurrence of patients with chronic subdural hematoma (CSDH). Methods: Eligible randomized controlled trials (RCTs) and prospective trials were searched in PubMed, Cochrane Library, and Embase, from database inception to Dec 2021. After screening the available studies following inclusion and exclusion criteria, strictly extract the main outcome measures. Taking the random-effects model, dichotomous data were determined and extracted by odds ratio (OR) with 95% Credible interval (CrI) and generated a surface under the cumulative ranking curve (SUCRA) to calculate the ranking probability of comparative effectiveness among each drug intervention. Moreover, we used the node-splitting model to evaluate inconsistency between direct and indirect comparisons of our NMA. Funnel plots were used to evaluate publication bias. Results: From the 318 of initial citation screening, 11 RCTs and 3 prospective trials (n=3456 participants) were ultimately included in our study. Our NMA results illustrated that atorvastatin + dexamethasone (ATO+DXM) (OR=0.06, 95%CrI 0.01,0.89) was the most effective intervention to improve the recurrence of patients with CSDH (SUCRA=89.40%, 95%CrI 0.29-1.00). Four drug interventions [ATO+DXM (OR=0.06, 95%CrI 0.01,0.89), DXM (OR=0.18, 95%CrI 0.07, 0.41), tranexamic acid (TXA) (OR=0.26, 95%CrI 0.07, 0.41) and ATO (OR=0.41, 95%CrI 0.12, 0.90)] achieved significant statistical significance in improving the recurrence of CSDH patients compared with the placebo (PLB) or standard neurosurgical treatment (SNT) group. Conclusions: Our network meta-analysis (NMA) showed that ATO+DXM, DXM, ATO, and TXA both had definite efficacy in improving the recurrence of CSDH patients. Among them, ATO+DXM is the best intervention for improving the recurrence of patients with CSDH in this particular population. Multicenter rigorous designed prospective randomized trials are still needed to evaluate the role of various drugs intervention in improved neurological function or outcome.